Uniform doping of graphene close to the Dirac point by polymer-assisted assembly of molecular dopants - Hans He (Nature Portfolio, 2018)
Incorporating dopants in the graphene lattice to tune its electronic properties is a challenging task. Here, the authors report a strategy to dope epitaxial large-area graphene on SiC by means of spin-coating deposition of F4TCNQ polymers in ambient conditions.